Kemampuan produk bioinsektisida komersial berbahan aktif Metarhizium sp. dalam menyebabkan kematian larva Oryctes rhinoceros L. - Fakhrurreza, Moch Fakhmi; Fitriana, Yuyun; Suharjo, Radix; Swibawa, I Gede (Jurnal Proteksi Agrikultura, 2024)
The rhinoceros beetle (Oryctes rhinoceros L.) (Coleoptera: Scarabaeidae) is a significant pest reported to attack nearly all coconut and oil palm plantations in Indonesia. Metarhizium sp., a well-known biological control agent, has broad-spectrum insecticidal properties due to its production of destruxin toxins, which are particularly toxic to O. rhinoceros. However, the effectiveness of dry-formulation bioinsecticides containing Metarhizium for controlling this pest has not yet been fully assessed. Therefore, this study was conducted to evaluate the potential of a dry-formulated Metarhizium sp. bioinsecticide to induce mortality in O. rhinoceros larvae. The research objectives were: 1) to assess the ability of the dry formulation bioinsecticide with Metarhizium as the active ingredient to induce mortality in O. rhinoceros larvae; 2) to determine the most effective dose of the dry formulation bioinsecticide with Metarhizium sp. for causing high mortality rates in O. rhinoceros. The study employed a Completely Randomized Design (CRD) with five treatments: 37.5 g (P1), 28.13 g (P2), 18.75 g (P3), and 9.38 g (P4) of Metarhizium sp., along with a control (P5). Each experimental unit consisted of a 1000 ml jar containing 500 g of coconut stem powder and five O. rhinoceros larvae, replicated five times with a total of 125 larvae. Analysis was conducted using the LSD test at a 5% significance level. Results indicated that the bioinsecticide was effective, with the most effective dose being 18.75 g, which resulted in 76.00% mortality.